How do u solve (f-g)(x) when f(x)=4x/7 +7 and g(x)=-6/x

Ok so its (f-g)(x)=4x/7 +7 - (-6/x)
But how do u simplify it from there?

Thanks!

1 answer

4x/7 + 7 + 6/x

That looks simple enough to me, but some folks like to have a single rational function:

multiply to get everything over a common denominator of 7x:

(4x^2 + 49x + 42)/7x
Similar Questions
  1. 1. Solve for x.4(x - b) = x b = 4/3x b = 3/4x x = 4/3b x = 3/4b 2. Solve for y, then find the value of y when given x = 2. 6x =
    1. answers icon 14 answers
    1. answers icon 1 answer
  2. please check my homeworkc1. Solve 3x – 19 = 2 Ax = -17 Bx = -17/3 Cx = 7 Dx = -51 Ex = 20 Fx = 18 b2. Solve 4x + 12x = 62 +
    1. answers icon 6 answers
  3. Solve the indicated variable:1. Volume of a cone: solve for h: V=¨ir^2h/3 2. Temperature formula: solve for C: F=9/5C+32
    1. answers icon 1 answer
more similar questions